Optimal Factor Setting to Reduce Problem from Lead Bridging by Using Design of Experiments: A Case Study of Electronics Part Factory - Vongpeng, Somporn; Prasunjai, Anyarat (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to reduce lead bridging waste in the PCB assembly process by the optimal factor setting. The total amount of wastes in a production process at a case study company was 2.58 percent including the major problem of the short-circuit of CPU position problem giving the amount of waste of 1.85 percent. The steps of waste reduction were based on the Pareto chart to order the problem causing waste production and also used the cause – effect diagram to analyze the problem and the design of experiments (DOE) method in order to obtain the suitable factors. Two effective factors in the DOE method were the hole size of stencil block factor varying at 0.25 and 0.30 millimeters and the board size height factor varying at 0.50 and 1.0 millimeters. The result of this research showed that the appropriate parameters to set up the machine were the hole size of stencil block factor of 0.25 millimeters and the board size height of 0.50 millimeters. After the experiment, it showed that the lead bridging wastes were eliminated from 1.85 percent to zero resulting in the reduction of the total amount of waste to be 0.35 percent due to a decrease in waste in other production processes. Therefore, after improving the factors of production, the total amount of waste was in line with the target set.